A Novel Pyroptosis-related Prognostic Model for Hepatocellular Carcinoma - Wu, Qianqian; Jiang, Sutian; Cheng, Tong; Xu, Manyu; Lu, Bing (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC) is the second most lethal malignant tumor due to its extreme heterogeneity and complicated molecular. Novel prognostic biomarkers are urgently needed since no effective and reliable prognostic biomarkers currently for HCC patients. Growing evidences revealed that pyroptosis plays a role in the occurrence and the progression of malignant tumors. However, the relationship between pyroptosis-related genes（PRGs）and prognosis of HCC patients remains unclear. In this study, 57 PRGs were obtained from previous studies and GeneCards database. The gene expression profiles coupled with clinical data of HCC patients were acquired from public data portals. The LASSO Cox regression analysis was performed to establish a risk model in TCGA. In addition, the risk model was further validated in an independent ICGC dataset. Our result showed that thirty-nine PRGs were significantly differentially expressed between tumor and normal liver tissues in TCGA cohort. The functional analysis confirmed that these PRGs were enriched in pyroptosis-related pathways. According to the univariate Cox regression analysis, fourteen of differentially expressed PRGs were correlated with the prognosis of HCC patients in TCGA. The risk model integrating two PRGs were constructed to classify the patients into different risk groups. A poor overall survival was revealed in the high-risk group of both TCGA (p<0.001) and ICGC (p<0.001) patients. The receiver operating characteristic (ROC) curve demonstrated the of the model. In addition, the risk score was confirmed as an independent prognostic indicator via multivariate Cox regression analysis (TCGA cohort：HR=3.346, p<0.001; ICGC cohort: HR=3.699, p<0.001).Moreover, the ssGSEA result showed the different immune status between high and low risk groups. In conclusion, a new pyroptosis-related risk model has the potential to be used in predicting prognosis of HCC patients.